Identification of a Functional fur Gene in Bradyrhizobium japonicum - Hamza, Iqbal (American Society for Microbiology, 1999)
The recent identification of the iron response regulator (Irr) in Bradyrhizobium japonicum raised the question of whether the global regulator Fur is present in that organism. A fur gene homolog was isolated by the functional complementation of an Escherichia coli fur mutant. The B. japonicum Fur bound to a Fur box DNA element in vitro, and a fur mutant grown in iron-replete medium was derepressed for iron uptake activity. Thus, B. japonicum expresses at least two regulators of iron metabolism.